An Interscholastic Network To Generate LexA Enhancer Trap Lines in Drosophila. Issue 7 (1st July 2019) - Kockel, Lutz; Griffin, Catherine; Ahmed, Yaseen; Fidelak, Lauren; Rajan, Arjun; Gould, Ethan P; Haigney, Myles; Ralston, Benjamin; Tercek, Rex J; Galligani, Lara; Rao, Sagar; Huq, Lutfi; et al.
Abstract: Binary expression systems like the LexA-LexAop system provide a powerful experimental tool kit to study gene and tissue function in developmental biology, neurobiology, and physiology. However, the number of well-defined LexA enhancer trap insertions remains limited. In this study, we present the molecular characterization and initial tissue expression analysis of nearly 100 novel StanEx LexA enhancer traps, derived from the StanEx 1 index line. This includes 76 insertions into novel, distinct gene loci not previously associated with enhancer traps or targeted LexA constructs. Additionally, our studies revealed evidence for selective transposase-dependent replacement of a previously-undetected KP element on chromosome III within the StanEx 1 genetic background during hybrid dysgenesis, suggesting a molecular basis for the over-representation of LexA insertions at the NK7.1 locus in our screen. Production and characterization of novel fly lines were performed by students and teachers in experiment-based genetics classes within a geographically diverse network of public and independent high schools. Thus, unique partnerships between secondary schools and university-based programs have produced and characterized novel genetic and molecular resources in Drosophila for open-source distribution, and provide paradigms for development of science education through experience-based pedagogy.